MicroRNA-92a Regulates Expression of Kruppel-like Factor2 in Rabbit Model of Intracranial Aneurysm - Wu, X; Zhang, J; Huang, Q; Yang, P; Chen, J; Liu, J (Cellular and Molecular Biology, 2015)
To explore role of miRNA-92a in regulation of KLF2 expression in intracranial aneurysm model, real time PCR, IHC, ISH and luciferase activity were used to test relationship of miR-92a and KLF2. The results demonstrated that KLF2 showed a time-dependent increase following development of IA model, but the miR-92a showed a time-dependent decrease, co-expression of miR-92a was found to effectively down-regulate luciferase expression in constructs with 3"²UTRs of KLF2, to determine the functions of miR-92a in rabbit ECs, we transfected the pre-miR-92a into rabbit ECs for over-expression, the results showed that the protein level of KLF2 was significantly down-regulated when over-expression of miR-92a. In conclusion, our research demonstrated that miR-92a and KLF2 were negative correlation in intracranial aneurysm model, and miR-92a could directly target KLF2 in endothelial cells through complementary sequence of 3"²UTR region.